2004
DOI: 10.1037/0893-164x.18.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Substance Use Treatment Outcomes of Adolescents.

Abstract: Treatment outcomes of 126 adolescents (13-18 years old) with comorbid substance use disorders (SUDs) and Axis I psychiatric disorders (mood, anxiety, conduct, and attention-deficit/hyperactivity disorders) were compared to 81 SUD adolescents with no additional Axis I disorder. Participants completed structured interviews and symptom measures while participating in an adolescent treatment program and at 6 months following treatment. Results indicated that comorbid youth received more treatment during the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
5
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 51 publications
5
92
5
1
Order By: Relevance
“…As noted in the introduction, several studies have shown the prognostic significance of co-occurring conduct disorder for drug-abusing youth (Brown, Gleghorn, Schuckit, Myers, & Mott, 1996;Crowley et al, 1998;Myers et al, 1995;Tomlinson, Brown, & Abrantes, 2004). An additional contribution of this study to this comorbidity literature is that our follow-up period is longer than the more typical shorter term follow-up periods in the literature, and we included a community-based control group.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the introduction, several studies have shown the prognostic significance of co-occurring conduct disorder for drug-abusing youth (Brown, Gleghorn, Schuckit, Myers, & Mott, 1996;Crowley et al, 1998;Myers et al, 1995;Tomlinson, Brown, & Abrantes, 2004). An additional contribution of this study to this comorbidity literature is that our follow-up period is longer than the more typical shorter term follow-up periods in the literature, and we included a community-based control group.…”
Section: Discussionmentioning
confidence: 99%
“…70 Strong evidence exists for adolescent alcohol involvement directly causing physical outcomes such as blackouts, unplanned sexual behavior, and motor vehicle crashes. Less clear is the casual contribution of alcohol involvement to the multiple behavioral, emotional, social, and academic problems that are correlated with teen drinking.…”
Section: Effects Of Alcohol Use On Adolescent Developmentmentioning
confidence: 99%
“…Reviews of research on neurocognitive effects of alcohol on adolescents and college students, as well as animal models of adolescence, 6,70 concluded that adolescent alcohol use is associated with damage to the brain and neurocognitive deficits, with implications for learning and other cognitive abilities that may continue to affect the individual into adulthood. For example, adolescents with an AUD have deficits in memory retrieval and in visuospatial functioning.…”
Section: Alcohol and The Developing Adolescent Brainmentioning
confidence: 99%
See 2 more Smart Citations